2018
DOI: 10.1016/j.ijid.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

HACEK infective endocarditis: Epidemiology, clinical features, and outcome: A case–control study

Abstract: HACEK-IE represented 1.3% of all IE cases. Clinical features and outcomes were comparable to those of the VGS-IE control group. Despite the trend towards a larger vegetation size, the embolic event rate was not higher and the 1-year mortality was significantly lower for HACEK-IE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 20 publications
2
26
0
2
Order By: Relevance
“…This study is the largest one to date describing IE due to HACEK, and most of the features presented here are in line with previous findings by others. Importantly, this study confirms that IE caused by HACEK has a more favourable prognosis than IE caused by most other pathogens [5,7]. The mortality, however, was lower in our cohort as compared to the international cohort study [5], possibly reflecting that the present study is based on data from an entire country and not only on patients treated in tertiary centres.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This study is the largest one to date describing IE due to HACEK, and most of the features presented here are in line with previous findings by others. Importantly, this study confirms that IE caused by HACEK has a more favourable prognosis than IE caused by most other pathogens [5,7]. The mortality, however, was lower in our cohort as compared to the international cohort study [5], possibly reflecting that the present study is based on data from an entire country and not only on patients treated in tertiary centres.…”
Section: Discussionsupporting
confidence: 72%
“…In a relatively recent publication, 16 cases of IE due to HACEK, reported to a Spanish registry, were compared to cases of streptococcal IE reported to the same registry. The groups had many similarities, but the prognosis was significantly more favourable for cases of IE caused by HACEK [7].…”
Section: Introductionmentioning
confidence: 99%
“…Besides risk factors, few other similarities between non-meningococcal, non-gonococcal Neisseria species and HACEK bacteria exist. HACEK-IE vegetations have been shown on average to be larger compared to vegetations caused by viridans group streptococci (11.5 mm vs 9 mm), and these vegetations have higher rates of embolization [13]. Our patient was found to have a large vegetation (21 mm) and clinical evidence of embolization, further demonstrating the similarities between HACEK organisms and non-meningococcal, non-gonococcal Neisseria.…”
Section: Discussionsupporting
confidence: 52%
“…However, in the 1970s, research studies found that N. flavescens/subflava were capable of beta-lactamase production, thus rendering penicillin antibiotics largely ineffective [10]. Of note, studies of HACEK organisms also have shown their capability to synthesize beta-lactamase, making third-generation cephalosporins the primary antibiotic choice for HACEK-IE treatment [13]. Our patient was treated with cefepime, with subsequent repeat negative blood cultures and discharged on a longer course of ceftriaxone.…”
Section: Discussionmentioning
confidence: 84%
“…However, Campylobacter also accounts for 1% of the oral microbiome in the saliva of healthy adults [ 19 ] and this proportion was identical to our control group but lower in CRS patients. Cardiobacterium is a Gram-negative bacillus bacterium of the HACEK group (represents the species of Haemophilus, Aggregatibacter, Cardiobacterium, Eikenella, and Kingella) and accounts for 5–10% of infections in endocarditis patients who do not use intravenous drugs [ 45 , 46 ]. Currently, only two species of Cardiobacterium hominis and Cardiobacterium valvarum have been identified.…”
Section: Discussionmentioning
confidence: 99%